An Evaluation of Cholesterol Ingestion in Rabbits Infected with Trypanosoma cruzi - M Alarcón; N Añez; L Calderón; A Matousek (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2004)
In order to determine the possible effect of Trypanosoma cruzi infection and an atherogenic diet on the atherosclerosis-Chagas interaction in rabbits (Sylvilagus floridanus orinoci), a study was made. The animals were divided into four groups: I.- healthy control; II.- atherogenic (Colesterol 60mg/day)diet ; III.- atherogenic diet infected with Y strain subcutaneously(2x10 bloodstream trypomastigotes injected subcutaneously), and IV infected with T. cruzi infection. Total Cholesterol concentration (TC), low density (LDL) and high density lipoprotein (HDL) levels were measured in plasma using microenzymatic colorimetric analysis and analysis of variance (ANOVA) was applied to the results. The atherogenic diet produced a progressive increase of TC, LDL and HDL in groups II and III compared with the healthy and infected groups. TC, HDL and LDL levels were significantly lower (P 0.05) in group III with respect to group II rabbits. The reduction of TC suggests a diminished capacity of infected liver for lipoproteins to liberate and/or a greater peroxidation of HDL and LDL as an effect of the infection, with a consequent increase in cholesterol bile elimination. Finally, the results suggest that cholesterol diet and T. cruzi interaction could favor atherosclerosis disease. On the other hand, the endothelial damage caused by these parasites could favor the cholesterol deposit in the microvasculature and at the same time the lowerHDLlevels, produce an increase of the atherogenicity through a diet high in cholesterol.